Production of L-asparaginase through biodegradation of chicken bone wastes - Chia, Vi Vien (2017)
L-asparaginase is highly demanded in pharmaceutical, food and biosensor industry due to its remarkable properties in hydrolysing L-asparagine into aspartic acid and ammonia. Owing to this significant property, L-asparaginase is widely produced through microbial fermentation. This research aims to produce L-asparaginase enzyme through microbial fermentation by the most potent isolate in the presence of chicken bone wastes as the substrate. Therefore, this research can be categorised into 3 parts where the first part was to perform several studies in determining the best enzyme producer and substrate while the second part was the effect of process parameters using One-Factor-at-a-Time (OFAT) method and the third part was the purification and characterisation study of L-asparaginase. Six millilitres (5 x 108 cells/ml) of Escherichia coli ATCC 10536 is the optimum inoculum size in 50 ml of pH 9 growth media at 40 °C for 2 days. In addition to that, Escherichia coli ATCC 10536 was fully enhanced when it was engaged with 1.0 % w/v of starch, 0.2 % w/v of ammonium chloride and 1 % w/v of cooked chicken bone (CCB) as the carbon source, nitrogen source and substrate respectively. The effect of process parameters studied using OFAT method revealed that Escherichia coli ATCC 10536 is the most potent L-asparaginase producer in this research and it preferred nutrient broth as the growth media in producing L-asparaginase. Furthermore, Escherichia coli ATCC 10536 L-asparaginase was purified by ammonium sulfate precipitation, dialysis and DEAE-cellulose chromatography. At the end of purification, 0.42 % yield of L-asparaginase was obtained. In addition, the dialysed ammonium sulfate fraction of L-asparaginase was partially characterised which resulted to 40 °C, pH 8, Na+ and ethylenediaminetetraacetic acid (EDTA) being the optimum incubation temperature, pH, metal ion and inhibitor respectively. In conclusion, Escherichia coli ATCC 10536 is an excellent L-asparaginase producer when the fermentation is supplemented with high protein content of cooked chicken bone as substrate.